Is Cancer a different Disease in the developing World? - Itrat Mehdi,; Suad Sulaiman Al Kharusi, (Journal of the Pakistan Medical Association, 2024)
The mounting rise in figures of non-communicable diseases globally, is noticeably disproportionate in prevalence and mortality in low- and middle-income countries (LMICs). The epidemiologic trend of cancers in LMICs is of distinct apprehension. In 2018, an estimated 18.1 million new cancer cases were diagnosed and 9.6 million cancer deaths occurred. The WHO estimates that by 2040, this will increase to 29.5 million new cancer diagnoses and 16.5 million cancer-related deaths annually.1 Given the population boom and gradual increase in life expectancy in developing countries, a significant increase in cancer incidence in the developing world is projected. The rising figures of cancer and mortality are set to double, and more than 70% of new cancers will occur in people in the developing world.2 In 2030, cancer deaths in LMICs are estimated to increase from 65% to 75%.1,3 The higher income countries (HICs) have rising cancer incidence rates, but the mortality rate is significantly higher in lower- and middle-income countries (LMICs) and continue to rise, whereas mortality rates in HICs are either decreasing or stable. Despite a lower incidence, cancer-related mortality is significantly higher in younger patients in LMICs. This has an immense economic impact of premature mortality and lost years of productive life.3,4